Microbial Deterioration of Paints - T.C. , Ogu; A.I. , Okaa; A.C. , Ozokpo; C.C. , Onochie, (African Journal of Education,Science and Technology (AJEST), 2016)
Biodeteriorated painted surfaces and In-can paints in Onitsha, Anambra State of Nigeria were analysed. The effects of Biocides on the biodeteriogens were also investigated. Psueudomonas, Bacillus, Arthrobacter, Enterobacter, Staphylococcus, Micrococcus and Microbacterium were the bacterial genera isolated while Fusarium, Aspergillus niger, Aspergillus fumigates, Aternaria, Cladosporium and Mucor species Micrococcus and Fusarium were the fungal isolates. The frequency of occurrence of bacterial and fungal species of normal and biodeteriorated surfaces were found to be 90% for Aspergillus niger, 80% for Bacillus sp., 60% for Cladosporium sp.,40% for sp., 50% for Pseudomonas sp., 30% Alternaria sp., 20% for Arthrobacter, Enterobacter and Aspergillus fumigatus species. Enterobacter, Micrococcus, Bacillus, Pseudomonas, Aternaria, Fusarium, Cladosporium species and Aspergillus niger were able to utilize either of the paint samples (gloss and Emulsion paint) in the microbial challenge test. From the mean susceptibility of biodeteriogens to biocides, bacterial deteriogens were more responsive to biocides than the fungal deteriogens.